Perancangan Website Departement Profile Plant Hauling District Indo PT. Pamapersada Nusantara Kalimantan Timur - Fitri Damayanti; Wawan Joko Pranoto (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
One media for conveying information about a departement, company or agency is a website profile. To provide information, the indo plant hauling district departement only uses the WhatsApp application to share the latest news, announcements, or updates related to the departement, such as awards, new projects, or changes in the organization. To overcome the problem of information that can only be known by people in the departement, we provide recommendations for designing the Indo Plant Hauling District Departement website PT. Pamapersada Nusantara East Kalimantan. The prototype method that will be used to develop this website and get results from this service, namely a user interface design and website prototype for the Indo plant hauling district departement profile.